Functional Gene Expression in Shark Bay Hypersaline Microbial Mats: Adaptive Responses - Campbell, Matthew A.; Grice, Kliti; Visscher, Pieter T.; Morris, Therese; Wong, Hon Lun; White, Richard Allen; Burns, Brendan P.; Coolen, Marco J. L. (Frontiers in Microbiology, 2020)
Microbial mat communities possess extensive taxonomic and functional diversity, which drive high metabolic rates and rapid cycling of major elements. Modern microbial mats occurring in hypersaline environments are considered as analogues to extinct geobiological formations dating back to ~ 3.5 Gyr ago. Despite efforts to understand the diversity and metabolic potential of hypersaline microbial mats in Shark Bay, Western Australia, there has yet to be molecular analyses at the transcriptional level in these microbial communities. In this study, we generated metatranscriptomes for the first time from actively growing mats comparing the type of mat, as well as the influence of diel and seasonal cycles. We observed that the overall gene transcription is strongly influenced by microbial community structure and seasonality. The most transcribed genes were associated with tackling the low nutrient conditions by the uptake of fatty acids, phosphorus, iron, and nickel from the environment as well as with protective mechanisms against elevated salinity conditions and to prevent build-up of ammonium produced by nitrate reducing microorganisms. A range of pathways involved in carbon, nitrogen and sulfur cycles were identified in mat metatranscriptomes, with anoxygenic photosynthesis and chemoautotrophy using the Arnon-Buchanan cycle inferred as major pathways involved in the carbon cycle. Furthermore, enrichment of active anaerobic pathways (e.g., sulfate reduction, methanogenesis, Wood–Ljungdahl) in smooth mats corroborates previous metagenomic studies and further advocates the potential of these communities as modern analogues of ancient microbialites.